Identifications and comparison of volatile aroma constrituents of Salacca zalacca (Gaertn.) Voss Extrated by steam distillation, solvent extraction and supercritcal fluid extraction methods. - Mohd Mokhlesur, M.; Nur Nadhirah, H.; Zaidul, I.S.M.; Siti Zaiton, M.S. (2018)
Salacca zalacca (Gaertn.) Voss (salak fruit or snake fruit) is a species of palm tree native to Southwest Java and North Sumatra in Indonesia. It is known as one of the exotic fruits in Malaysia. It has a reddish brown scaly skin with pleasant pineapple, pear and banana-like aromas. Due to its pleasant aroma, S. zalacca has potential in perfumery and pharmaceutical industries. The volatile aromas of plants are usually extracted by conventional extraction method such as steam distillation and solvent extraction method . These methods are laborious, have incomplete extraction process, require long extraction time, and produced a lot of toxic chemical wastes. New extraction technique introduced by the researcher to overcome these limitations is supercritical carl>on dioxide extraction method (SC-CO2). This technique is available to extract the volatile aroma of the plants. It is rapidly gaining attention due to its superior benefits compared to the conventional extraction methods. It is considered as a green extraction technique because it is renewable, produces little to no toxic wastes and bas short extraction time. In this study, S. zalacca were extracted by steam distillation, solvent extraction and SC-CO,. Steam distillation was not a suitable extraction method for S. zalacca as it produced inorganic compound. The percentage yields of SC-CO, samples were higher (10 MPa, 30 •C:0.2704 %; 25 MPa, 50-C:03634 %; 40 MPa, 70 -C:02635 %) than the hexane (0.0511 %) and dicblorometbane (0.1358 %) extractions but lower than the diethyl ether (0.5692 %) solvent extraction. SFE has shorter extraction time and produced little chemical waste compared to solvent extraction method .GC-MS anal}is of the extracts from both extraction methods should be conducted to identify and compare the volatile aroma constituents present in solvent extraction extracts and SFE extracts.